Assembly and immunogenicity of baculovirus-derived infectious bronchitis virus–like particles carrying membrane, envelope and the recombinant spike proteins - Xu, Peng-wei (Biotechnol Lett, 2015)
OBJECTIVE: To assemble infectious bronchitis virus (IBV)-like particles bearing the recombinant spike protein and investigate the humoral immune responses in chickens. RESULTS: IBV virus-like particles (VLPs) were generated through the co-infection with three recombinant baculoviruses separately encoding M, E or the recombinant S genes. The recombinant S protein was sufficiently flexible to retain the ability to self-assemble into VLPs. The size and morphology of the VLPs were similar to authentic IBV particles. In addition, the immunogenicity of IBV VLPs had been investigated. The results demonstrated that the efficiency of the newly generated VLPs was comparable to that of the inactivated M41 viruses in eliciting IBV-specific antibodies and neutralizing antibodies in chickens via subcutaneous inoculation. CONCLUSIONS: This work provides basic information for the mechanism of IBV VLP formation and develops a platform for further designing IBV VLP-based vaccines against IBV or other viruses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10529-015-1973-3) contains supplementary material, which is available to authorized users.